Dhonburi Teachers' College, Thailand an institutional case study - Kantabut, Wanna 1939- (1972)
This special problem is an institutional case of Dhonburi Teachers' College, Thailand. It sought to describe the institutional components of the said institution in so far as its organizational structure and the curricula of the different programs are concerned.
Thesis (M. Ed.)--University of the Philippines.
Keywords: Dhonburi Teachers' College, Thailand